2020
DOI: 10.7150/jca.49970
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Accuracy and Prognostic Significance of the Dickkopf-1 Protein in Gastrointestinal Carcinomas: Systematic Review and Network Meta-analysis

Abstract: Objective: To evaluate the diagnosis accuracy and prognostic significance of bio-marker dickkopf-1(DKK-1) protein in GIC, and also sub-type of hepatocellular carcinoma (HCC), pancreas carcinomas (PC), oesophageal carcinoma (EPC) and Adenocarcinoma of esophago-gastric junction (AEGJ), etc. Methods: Electronic databases were searched from inception to May 2020. Patients were diagnosed with gastrointestinal carcinomas, and provided data on the correlation between high and low DK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The glycoprotein Dickkopf-1 (DKK-1), expressed mainly in the placenta and embryonic tissues, is an antagonist of the Wnt/β-catenin signaling pathway and is elevated in several cancer types. DKK-1 shows higher efficacy for detecting HCC than AFP in phase 4 trials ( 206 208 ), but midkine is more precise than DKK-1 in cirrhotic HCV patients ( 209 ). A combination of Golgi protein 73, AFP, and Dickkopf-1 increases the sensitivity and specificity of HCC detection ( 210 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…The glycoprotein Dickkopf-1 (DKK-1), expressed mainly in the placenta and embryonic tissues, is an antagonist of the Wnt/β-catenin signaling pathway and is elevated in several cancer types. DKK-1 shows higher efficacy for detecting HCC than AFP in phase 4 trials ( 206 208 ), but midkine is more precise than DKK-1 in cirrhotic HCV patients ( 209 ). A combination of Golgi protein 73, AFP, and Dickkopf-1 increases the sensitivity and specificity of HCC detection ( 210 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…( 115 , 116 ) However, the clinical utility of GP73 is limited by the lack of an FDA‐approved immunoassay that detects the specific glycosylated isoform associated with HCC. Other promising circulating biomarkers for the early diagnosis of HCC include osteopontin, ( 101 , 117 , 118 , 119 ) midkine, ( 120 , 121 , 122 , 123 , 124 ) Dickkopf‐1, ( 125 , 126 ) squamous cell carcinoma antigen, ( 127 , 128 ) and fibronectin. ( 129 , 130 ) These biomarkers need further validation in large, multicenter studies that include patients with HCCs arising from different etiologies.…”
Section: What Are the Current And Emerging Circulating Biomarkers For Hcc Surveillance?mentioning
confidence: 99%
“…In vitro and in vivo studies showed that activator protein-1 (AP-1) controlled tumor growth, progression and drug resistance[ 10 , 11 ]. DKK1 is a potent antagonist that suppresses oncogenic Wnt/β-catenin signaling and tumors by binding to the Wnt coreceptor: low-density lipoprotein receptor-related protein (LRP) 5/6[ 12 , 13 ]. However, recent studies demonstrated that DKK1 behaved like an oncogene in a variety of cancers[ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%